Monetary policy and currency wars: National economic interests vs international partnership - Svetlana Bekareva; Alexander Baranov; Ekaterina Meltenisova (European Regional Science Association (ERSA), 2016)
Introduction. The investigation is devoted to the issue of a national financial stability and economic growth. The theme of our investigation is topical because of the modern world economy processes. Some countries have been using different monetary, economic, and political instruments to stimulate growth of their national economies since the 2007 - 2009 world economic and financial crisis. Some developing countries began suffering from competitiveness losses of their national produces as a result of quantitative easing implemented by some developed countries such as, for example, the USA and Japan, or foreign exchange intervention by the central bank of Switzerland, in order to devaluate their national currencies. An aggressive monetary policy that aimed competitive devaluation led to the currency wars. Currency war is deliberate policy of manipulating exchange rates downwards to increase domestic competitiveness that takes place in many countries at the same time and can lead to economic crisis. What instruments can be used to manipulate exchange rates in the modern international monetary system? It depends on the exchange rate regime announced by a country. Nowadays developed countries mainly use interest rates as a key monetary instrument, and some of them apply a negative interest rate policy. Use of interest rates and quantitative easing by developing countries might have negative effect on the economy. Moreover, a key interest rate (or discount rate) in developing countries sometimes is just an indicator for banking system rates that can stimulate credit activity in a national economy. Specific objectives of the investigation are: 1) to determine effect of using different instruments of monetary policy by developed and developing countries; 2) to assess the results of implementing currency war methods in order to increase their national competitiveness for different countries. Statistical data has been found in the International Monetary Fund database. We applied indices connected with foreign exchange markets and monetary policy for about 50 countries including more than 20 countries which carry out monetary policy of competitive devaluation. Methods of investigation represent econometric analysis. Cluster and panel data analyses were used to determine groups of similar economies and the most powerful group of countries nowadays and find factors influenced competitiveness of regional and national economies connected with chosen indexes which show monetary policy effect. Results of the investigation are as follows. The methods and instruments of monetary policy are different for countries and they have been changing since 2007. They depend on the national and regional features of economic development. The key instrument for developed economies is supposed to be interest rates; not all of the countries with emerging markets can use them effectively. There are countries which have some advantages of currency wars but the global perspectives are vague. Conclusion is connected with determining of the perspectives of further changing in monetary policy by different countries, applying a negative interest rate policy, and currency wars expansion.
Keywords: F31; 330; monetary policy; economic growth; currency war